Examining Sports Endorsement/Sponsorship Campaigns' Effectiveness Towards: Cord-Cutters Brand Attachment - Souza, Tatum (2017)
The marketing world is being completely altered due to the increasing amount of content mediums being developed and used every day, forcing firms to come up with new ways to reach their consumers. However, brand exposure is not the only challenge companies are facing today. Due to globalization and increased competition, it has become increasingly important for companies to commit to their relationship with their consumers, and specifically invest time and effort into attaining brand attachment. Brand attachment has the ability to position brands in front of their increased competition and better sustain their financial success. Creating brand attachment through sports endorsement/sponsorship campaigns with professional athletes, is a popular marketing technique. The emergence of the cord-cutting generation is what originated the focus of this investigation - Marketers are still utilizing sports endorsement/sponsorship campaigns to develop brand attachment with the cord-cutting generation. However, the question is, whether sports endorsement/sponsorship campaigns are an effective marketing technique still? Do cord-cutting consumers get enough exposure to sports endorsement/sponsorship campaigns? And are they able to develop brand attachment due to the campaigns specifically that utilize professional athletes? After reviewing secondary data and primary data on the topic, the researcher was able to answer all the questions posed previously. The secondary data reviewed in the Literature Review chapter of this report, gave the researcher a better understanding of brand attachment and brand loyalty. The research of recognized brand specialists and their theories and concepts, were compared and contrasted. Due to the fact that cord-cutting is a relatively new phenomenon, there has been limited research done on the subject. Therefore, information pertaining to the generation in question, has been collected from non-published articles and to some extent blogs, by marketing researchers or people whom have a deep understanding of the cord-cutting generation. These articles are not of poor quality, and any information utilized was critically reviewed. All literature reviewed, guided this study and aided in the development and decision of the Methodology utilized. After the researcher Collected, Analysed and Discussed the data, supported Conclusions were able to be drawn, and the information gathered revealed Limitations of the research, that aided the researchers ability to make Future Recommendations. The conclusion the researcher of this study came to is; the cord-cutting generation are getting enough exposure to sports endorsement/sponsorship campaigns to develop brand attachment, based off the data collected. This information is valuable for companies investing heavily in sponsorship/endorsement campaigns, and reaffirms that company's marketing managers should continue to invest in this type of advertisement.